The impact of aerobic exercise dose based on ACSM recommendations on patients with Parkinson’s disease: a systematic review and meta-analysis of randomized controlled trials - Cui, Wenlai; Hu, Zepeng; Li, Jian; Wang, Siji; Xu, Ruilin (Frontiers in Aging Neuroscience, 2024)
Background: To explore the effects of different dose of aerobic exercise on motor function, balance, mobility, and quality of life in Parkinson's disease patients, aiming to provide insights into determining the optimal aerobic exercise dose for treating PD.Methods: Searching was conducted in four databases: PubMed, Embase, Web of Science, and Cochrane. The dose of aerobic exercise intervention was evaluated based on the recommendations of the American College of Sports Medicine regarding the development and maintenance of cardiorespiratory health, muscle strength, and functional mobility in patients with PD. The exercise intervention dose of the included studies were first classified into high ACSM compliance and low ACSM compliance based on meeting 4/6 of the ACSM recommendations. The reliability of the results was then validated using the criterion of meeting 5/6 of the ACSM recommendations.Comparisons of the effects of aerobic exercise dose on Motor function, Balance, Mobility, and QOL in PD patients using standardized mean difference with 95% confidence intervals.Results: When using the 4/6 ACSM compliance criterion, 17 studies were categorized as high ACSM compliance and 12 as low ACSM compliance. The SMD ratios for high versus low ACSM compliance were: UPDRS-III (-0.79: -0.18), BBS (0.60: 0.05), TUG (-0.60: -0.60), and QOL (-1.05: -0.15). When using the 5/6 ACSM compliance criterion, 11 studies were categorized as high ACSM compliance and 19 as low ACSM compliance. The SMD ratios for high versus low ACSM compliance were: UPDRS-III (-0.95: -0.38), BBS (0.48: 0.37), TUG (-0.71: -0.55), and QOL (-0.7: 0.04). Conclusions: This study provides preliminary support for the potential of aerobic exercise to improve certain clinical symptoms in patients with PD. Furthermore, the results indicate that compliance to higher doses of aerobic exercise, as per ACSM standards, may contribute to improvements in motor function, balance, mobility, and quality of life for patients with PD. However, due to the heterogeneity in the studies and the influence of factors that have not yet been fully explored, these conclusions should be interpreted with caution. More high-quality randomized controlled trials are needed in the future to further verify and clarify the effects of aerobic exercise.